Deep-frying oil induces cytotoxicity, inflammation and apoptosis on intestinal epithelial cells - Li, Xue; Nian, Bin-Bin; Tan, Chin-Ping; Liu, Yuan-Fa; Xu, Yong-Jiang (John Wiley & Sons, 2022)
BACKGROUND: Deep-frying oil has been found to cause inflammatory bowel disease (IBD). However, the molecular mechanism of the effect of deep-frying palm oil on IBD still remains undetermined. RESULTS: In the present study, bioinformatics and cell biology were used to investigate the functions and signal pathway enrichments of differentially expressed genes. The bioinformatics analysis of three original microarray datasets (GSE73661, GSE75214 and GSE126124) in the NCBI-Gene Expression Omnibus database showed 17 down-regulated genes (logFC < 0) and 2 up-regulated genes (logFC > 0) existed in the enteritis tissue. Meanwhile, pathway enrichment and protein–protein interaction network analysis suggested that IBD is relevant to cytotoxicity, inflammation and apoptosis. Furthermore, Caco-2 cells were treated with the main oxidation products of deep-frying oil-total polar compounds (TPC) and its components (polymerized triglyceride, oxidized triglycerides and triglyceride degradation products) isolated from deep-frying oil. The flow cytometry experiment revealed that TPC and its components could induce apoptosis, especially for oxidized triglyceride. A quantitative polymerase chain reaction analysis demonstrated that TPC and its component could induce Caco-2 cell apoptosis through AQP8/CXCL1/TNIP3/IL-1. CONCLUSION: The present study provides fundamental knowledge for understanding the effects of deep-frying oils on the cytotoxic and inflammatory of Caco-2 cells, in addition to clarifying the molecular function mechanism of deep-frying oil in IBD.